2016
DOI: 10.12659/msm.896768
|View full text |Cite
|
Sign up to set email alerts
|

Biallelic and Triallelic 5-Hydroxytyramine Transporter Gene-Linked Polymorphic Region (5- HTTLPR) Polymorphisms and Their Relationship with Lifelong Premature Ejaculation: A Case-Control Study in a Chinese Population

Abstract: BackgroundThis study aimed to explore the relationship between premature ejaculation (PE) and the serotonin transporter gene-linked polymorphic region (5-HTTLPR) with respect to the biallelic and triallelic classifications.Material/MethodsA total of 115 outpatients who complained of ejaculating prematurely and who were diagnosed as having lifelong premature ejaculation (LPE) and 101 controls without PE complaint were recruited. All subjects completed a detailed questionnaire and were genotyped for 5-HTTLPR pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Studies found that humans who carried gene polymorphisms in the SERT promoter region (5‐HTTLPR), where a 44‐base pair in the SERT insertion/deletion sequence underlies the short ( S ) allelic variant and long ( L ) allelic variant, lead to differential SERT expression levels (Lesch et al, ; Little et al, ). Given that, a number of studies were designed to explore the SERT promoter region polymorphisms(5‐HTTLPR) on PE in humans(Huang et al, ; Janssen et al, ; Jern, Eriksson, & Westberg, ; Ozbek et al, ; Peng et al, ; Zuccarello et al, ). However, these researchers’ results were contradictory and failed to identify the actual 5‐HTTLPR genetic loci that contributed to PE aetiology.…”
Section: Discussionmentioning
confidence: 99%
“…Studies found that humans who carried gene polymorphisms in the SERT promoter region (5‐HTTLPR), where a 44‐base pair in the SERT insertion/deletion sequence underlies the short ( S ) allelic variant and long ( L ) allelic variant, lead to differential SERT expression levels (Lesch et al, ; Little et al, ). Given that, a number of studies were designed to explore the SERT promoter region polymorphisms(5‐HTTLPR) on PE in humans(Huang et al, ; Janssen et al, ; Jern, Eriksson, & Westberg, ; Ozbek et al, ; Peng et al, ; Zuccarello et al, ). However, these researchers’ results were contradictory and failed to identify the actual 5‐HTTLPR genetic loci that contributed to PE aetiology.…”
Section: Discussionmentioning
confidence: 99%
“…In these studies we have included, just one study discussed the relationship with Chinese and suggested that triallelic way should be used in studying 5-HTTLPR (20). In addition, Safarinejad et al and Zuccarello et al also used triallelic approach to study 5-HTTLPR.…”
Section: Discussionmentioning
confidence: 99%
“…We excluded 42 studies: 10 were about the relation between the polymorphism of PE with medicine response; 19 were about other single nucleotide polymorphisms (SNPs) with PE; 2 were review; 11 were comments and responses. Finally, our meta contained 8 studies, a total of 898 LPE patients and 706 health controls (14,15,(20)(21)(22)(23)(24)(25). The basic characteristics of all studies were showed in Table 1.…”
Section: Studies Characteristicsmentioning
confidence: 99%
“…Several efforts were conducted in the last decades to investigate the relationship between 5‐HTTLPR polymorphisms and the susceptibility to PE which had yielded inconsistent results in different population (Huang et al., 2016; Janssen et al., 2009; Khan et al., 2018; Ozbek et al., 2009; Safarinejad, 2009; Zuccarello et al., 2012). Besides, studies in psychiatric disorders had shown that 5‐HTTLPR polymorphism was associated with the response to SSRI treatment (Illi et al., 2011; Manoharan et al., 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Several efforts were conducted in the last decades to investigate the relationship between 5-HTTLPR polymorphisms and the susceptibility to PE which had yielded inconsistent results in different population (Huang et al, 2016;Janssen et al, 2009;Khan et al, 2018;Ozbek et al, 2009;Safarinejad, 2009;Zuccarello et al, 2012).…”
mentioning
confidence: 99%